Pengaruh Penggunaan Media Poster Bergambar Terhadap Perkembangan Kognitif dan Bahasa Anak di RA Bina Mujtama - Anisya Ramadanty; Muhammad Syahrir Yudawan (LP3M STAI MA'ARIF MAGETAN, 2026)
This study aims to develop children’s cognitive and language abilities. One effective approach to optimizing development in these two aspects is the use of illustrated poster media. Children tend to be more engaged in learning activities that are rich in colors and images, which facilitates the achievement of targeted developmental outcomes. This media is designed as creatively as possible to attract children’s interest in learning numbers more effectively and to enhance their language skills through storytelling methods based on everyday activities.This research employs a quantitative approach using a quasi-experimental design, involving both an experimental class and a control class. The sample was selected using a purposive sampling technique, consisting of 20 students at RA Bina Mujtama.The results of the study indicate that, after conducting pre-tests and post-tests, the control class showed significant and effective improvement, with noticeable differences between pre-test and post-test scores. Therefore, it can be concluded that illustrated poster media has a significant effect on the cognitive and language development of children at RA Bina Mujtama.